Iron metabolism in colorectal cancer - Huang, Luji; Li, Wangji; Lu, Yan; Ju, Qinuo; Ouyang, Manzhao (Frontiers in Oncology, 2023)
Iron, as one of the essential trace elements in the human body, is involved in a wide range of critical biochemical reactions and physiological processes, including the maintenance of the normal cell cycle, mitochondrial function, nucleotide metabolism, and immune response. In this context, iron is naturally associated with cancer occurrence. Cellular iron deficiency can induce apoptosis, but excessive iron can produce many reactive oxygen species and damage biological macromolecules. Studies suggest that dietary iron, particularly heme iron, may be one of the leading causes of colorectal cancer (CRC). Moreover, patients with CRC have abnormal iron absorption, storage, utilization, and exportation. Therefore, iron is crucial for the development and progression of CRC. Elaborating on the alterations in iron metabolism during the onset and advancement of CRC would help to further explain the role and mechanism of iron inside the body. Thus, we reviewed the alterations in numerous iron metabolism-related molecules and their roles in CRC, which may provide new clues between iron metabolism and CRC.